Analysis of fiber nonlinearity for various power levels in DWDM system - Mad Zaki @ Abdullah, Shahrul Radzi (2013)
DWDM technology is known as a kind of technology for coupling and transmitting an optical signals of different wavelength over the same fiber. Such technology is important in order to expand the capacity of optical fiber communication system and to meet the growing demands of bandwidth. However, there are some limiting factors related to the data rate and capacity in DWDM system. These limiting factors can be linear or nonlinear. Theoretically, the nonlinearities in fiber arise as the number of data channel, transmission length, data rate and input power level increase. In this project, the objective is focused towards analyzing on the nonlinearities effect by compensating the linear effect in the fiber. Dispersion Compensation Fiber (DCF) and linear loss EDFA compensation have been used in single mode fiber (SMF) channel to ensure the communication quality for the design. The proposed DWDM transmission system with 8, 16 and 32 channels for 10Gbps with a channel spacing of 0.8nm was designed and simulated using Optisystem software. The BER performance with various input power levels in the range of -10dBm up to 10dBm, and fiber length greater than 50km are analyzed. It has been shown that for fixed length of the fiber, the only variable that can be manipulated to lower the nonlinear contribution is the input power. The higher the input power the higher the nonlinear contribution. However, if the input power is low, the bit rate should be low to maintained transmission at the expected BER (BER < 10-12).